Persepsi Generasi Muda Berdasarkan Proses Kognitif Terhadap Pertanian: Studi Pada Mahasiswa Baru - Aprilia, Anisa; Pariasa, Imaniar Ilmi; Dewi, Heptari Elita; Hardana, Andrean Eka (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
This reserach aims to analyze the factors influencing the younger generation's perception of agriculture based on accepted cognitive processes and the influence of the perception factors on the interest of the younger generation to work in the agricultural sector. The research survey was conducted on new students from the faculty of agriculture after they attended student orientation. While the analysis used is descriptive analysis, factor analysis, and logistic regression analysis, which have previously been tested for the validity and reliability of research data. The research finding is that there are three main factors in the perception of the younger generation towards agriculture, namely individual perceptions, economic perceptions, and socio-cultural perceptions. In the meantime, only the economic perception factor has a big effect on young people's desire to work in agriculture.Â